Growth and Competitive Analysis of SMEs in Sleman, Indonesia - Yunita Anggarini; Ahmad Maulin Naufa (Universitas Islam Sultan Agung, 2022)
This study examines the factors that affect the growth and competitiveness of Small and Medium Enterprises (SMEs) in Sleman Regency Yogyakarta Indonesia. We collect the data using a survey technique involving 100 SMEs’owners from five sectors (the craft, food processing, clothes, metals, and others). Regression analysis was used to analyze the relationship between internal and external factors and the performance of SMEs. The findings depict that both internal factors (entrepreneur attitudes towards risk, learning entrepreneurship, the number of employees, financial reports, wealth value, age, and license) and external factors (marketing networks and supplier cooperation) affect the performance growth and competitiveness of SMEs. This paper recommends that in order to develop the business activities of SMEs, the efforts include easy access to capital, business scale, network, marketing and partnership, human resources (knowledge of marketing, product development, license, financial reports, supply chain, risk management, business management, and others) could increase the technology access of product development to establish a more conducive business climate and more systematic strategy assistance based on the specific problems faced by SMEs.